FORCED DISPLACEMENT AND CHANGING SOCIO-ECONOMIC STATUS OF MIGRANT WOMEN IN THE URBAN KURDISH COMMUNITIES OF ISTANBUL - Eres, Gizem Damla; Koraltürk, Nurşen Gürboğa (PEOPLE: International Journal of Social Sciences, 2015)
In this paper I explain the changes in migrant Kurdish women’s socio-economic status who were forcibly displaced from their hometowns as a result of the conflict between PKK (Kurdistan Workers' Party) and TAF (Turkish Armed Forces) in the 1990’s. As part of my ongoing research, so far I have gone through a select bibliography and conducted field research which includes in-depth interviews with internally displaced Kurdish women residing in three neighborhoods of Istanbul. This paper reveals what it means for Kurdish women to withdraw from production, which they used to participate actively in the rural areas prior to internal displacement. Most of the interviewees are housewives who are neither formally nor informally integrated into the economic life. Despite their withdrawal from production in the rural setting, enhancement of social capital through their membership in the People’s Democratic Party (HDP) enables Kurdish women’s access to assets and networks in the city that are vital to the maintenance of household livelihood. This paper shows that internal displacement has been instrumental in creating opportunities for Kurdish migrant women to transform their social capital through political activism in the city and to realize their capabilities as manifested in the field of livelihood.